Improvement of a suction air cooling method for combined cycle power plants using water spray and its application to working plants - Shuichi UMEZAWA (The Japan Society of Mechanical Engineers, 2016)
Output increase of combined cycle power plants is highly expected in order to deal with tight supply-demand situation of electricity and to save fuel consumption. This paper reports improvement of the output increase method by cooling their suction air using water spray nozzles. The spray nozzles installed previously are pointing to downstream of air flow or downward. We tried to improve its cooling efficiency by optimizing the spray nozzle angle. Laboratory experiments were conducted for that purpose. Suction air area was 2 meter square, and air flow velocity was set to approximately 2 meter/sec. by a blower. Temperature and relative humidity were set to 33 degrees centigrade and 60 percent respectively by air-conditioning units. As a result, a method that the spray nozzles are pointing upstream of air flow showed the best performance. The same tendency was also observed by finite volume analysis using a CFD program. This method was applied at both a working combined cycle power plant of 380 MW and that of 500 MW on trial. Temperature of cooled air was measured using a number of thermocouples set in suction air room at each plant. Consequently, it was observed that the cooling efficiency was improved by ten percent and several percent respectively, and plant output was increased by approximately 2 MW at the 380 MW plant.